Embedded portable device for herb leaves recognition using image processing techniques and neural network algorithm - Zulkifli, Husin; Ali Yeon, Md Shakaff, Prof. Dr.; Abdul Halis, Abdul Aziz; Rohani, S. Mohamed Farook; Mahmad Nor, Jaafar, Assoc. Prof. Dr.; Uda, Hashim, Prof. Dr.; Azizi, Harun (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/